Prospects for the Development of the Environmental Responsibility System: Recommendations and Proposals (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this scientific article, the author presents environmental expertise as an important legal institution in ensuring environmental protection and sustainable development in Uzbekistan.